Box-Jenkins Modeling of Greek Stock Prices Data - Dritsaki, Chaido (International Journal of Economics and Financial Issues, 2015)
Recent econometric procedures are employed in this paper to investigate the behavioral properties of Athens Stock Exchange (ASE) indices. The results of serial correlation showed that the hypothesis of weak - form efficiency of Athens Stock Exchange should be rejected. The Augmented Dickey- Fuller tests and Phillips-Perron tests confirm the existence of unit root on levels of stock prices. The random walk hypothesis matches with ARIMA (0,1,2) model where the future values of stock prices cannot be defined from past values. Afterwards, the results of Theil Inequality Coefficient indices showed that the forecasting ability of the model is not satisfactory. Keywords: Market efficiency; ARIMA models; Stationary and Random Walk Tests; Stock prices; Forecasting; Greece JEL Classifications: C53; E27